Progressive macular hypomelanosis: a common disorder rarely diagnosed in clinical practice - Marta Pelc; Radomir Reszke; Jacek Szepietowski (Termedia Publishing House, 2016)
Introduction . Progressive macular hypomelanosis (PMH) is a cutaneous pigmentary disorder resulting from a deficit of melanin and manifesting with disseminated hypopigmented macules. Pityriasis alba, post-inflammatory hypopigmentation (atopic dermatitis, psoriasis), bacterial and fungal infections, neoplasms, vitiligo, piebaldism, nevus anemicus and idiopathic guttate hypomelanosis are included in the differential diagnosis. No commonly accepted therapeutic recommendations have been published so far; topical antibiotics, phototherapy and oral isotretinoin have been described in the literature. Objective. To present our own cases of PMH - a dermatosis which is somewhat common in the general population but is still diagnosed infrequently in clinical practice. Case report . We present two cases of PMH - a 33-year-old woman and a 38-year-old man in whom the diagnosis of PMH was established due to clinical examination and excluding other causes. The patients were treated with oral isotretinoin. Conclusions . Dermatologists should be aware of this entity; despite presenting with a somewhat benign course, PMH may pose a serious issue for the affected patients.